Management of atrial fibrillation in the emergency room and in the cardiology ward: the BLITZ AF study. Issue 2 (27th July 2018) - Gulizia, Michele Massimo; Cemin, Roberto; Colivicchi, Furio; De Luca, Leonardo; Di Lenarda, Andrea; Boriani, Giuseppe; Di Pasquale, Giuseppe; Nardi, Federico; Scherillo, Marino; Lucci, Donata; Fabbri, Gianna; Maggioni, Aldo Pietro; et al.
Abstract: Aims: To assess the number of admissions to the emergency room (ER) of patients with atrial fibrillation (AF) or atrial flutter (af) and their subsequent management. To evaluate the clinical profile and the use of antithrombotics and antiarrhythmic therapy in patients with AF admitted to cardiology wards. Methods and results: BLITZ-AF is a multicentre, observational study conducted in 154 centres on patients with AF/af. In each centre, data were collected, retrospectively for 4 weeks in ER and prospectively for 12 weeks in cardiology wards. In ER, there were 6275 admissions. Atrial fibrillation was the main diagnosis in 52.9% of the cases, af in 5.9%. Atrial fibrillation represented 1.0% of all ER admissions and 1.7% of all hospital admissions. A cardioversion has been performed in nearly 25% of the cases. Out of 4126 patients, 52.2% were admitted in cardiology ward; mean age was 74 ± 11 years, 41% were females. Patients with non-valvular AF were 3848 (93.3%); CHA2 DS2 -VASc score was ≥2 in 87.4%. Cardioversion was attempted in 38.8% of the patients. In-hospital mortality was 1.2%. At discharge, 42.6% of the patients were treated with vitamin K antagonists, 39.5% with direct oral anticoagulants, 13.6% with other antithrombotic drugs, and 4.2% did not take any antithrombotic agent. Rate control strategy was pursued in 47.2%, rhythm control in 44.0%, 45.6% were discharged in sinus rhythm. Conclusion: Atrial fibrillation still represents a significant burden on health care system. Oral anticoagulant use increased over time even if compliance with guidelines, with respect to prevention of the risk of stroke, remains suboptimal.